Does the Amniotic Fluid of Mice Contain a Viable Microbiota? - Winters, Andrew D.; Romero, Roberto; Greenberg, Jonathan M.; Galaz, Jose; Shaffer, Zachary D.; Garcia-Flores, Valeria; Kracht, David J.; Gomez-Lopez, Nardhy; Theis, Kevin R. (Frontiers in Immunology, 2022)
The existence of an amniotic fluid microbiota (i.e., a viable microbial community) in mammals is controversial. Its existence would require a fundamental reconsideration of fetal in utero exposure to and colonization by microorganisms and the role of intra-amniotic microorganisms in fetal immune and physiological development, as well as pregnancy outcomes. In this study, we determined whether the amniotic fluid of mice harbors a microbiota in late gestation. The bacterial profiles of amniotic fluids of pups located proximally or distally to the cervix were characterized through quantitative real-time PCR, 16S rRNA gene sequencing, and culture (N = 21 dams). These profiles were compared to those of technical controls for bacterial and bacterial DNA contamination. The load of 16S rRNA genes in the amniotic fluid exceeded that in controls. Additionally, the 16S rRNA gene profiles of the amniotic fluid differed from those of controls, with Corynebacterium tuberculostearicum being differentially more abundant in amniotic fluid profiles; however, this bacterium was not cultured from amniotic fluid. Of the 42 attempted bacterial cultures of amniotic fluids, only one yielded bacterial growth – Lactobacillus murinus. The 16S rRNA gene of this common murine-associated bacterium was not detected in any amniotic fluid sample, suggesting it did not originate from the amniotic fluid. No differences in 16S rRNA gene load, 16S rRNA gene profile, or bacterial culture were observed between amniotic fluids located proximal and distal to the cervix. Collectively, these data indicate that, although there is a modest DNA signal of bacteria in murine amniotic fluid, there is no evidence that this signal represents a viable microbiota. While this means that amniotic fluid is not a source of microorganisms for in utero colonization in mice, it may nevertheless contribute to fetal exposure to microbial components in utero. The developmental consequences of this warrant further investigation.